2018
DOI: 10.5812/iranjradiol.79503
|View full text |Cite
|
Sign up to set email alerts
|

Vena Cava and Left Renal Vein Variations and Association with Other Anomalies Including Horseshoe Kidney

Abstract: Objectives: The purpose of this study was to detect the types and prevalences of vena cava variations, as well as looking for gender differences and associating anomalies. Patients and Methods: The computed tomography (CT) images of 5763 patients who had undergone thorax and abdominal CT examinations were evaluated retrospectively for superior vena cava (SVC), inferior vena cava (IVC), and left renal vein (LRV) variations. Results: Vena cava variations were detected in 637 (11%) patients. SVC variations were p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

1
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 22 publications
1
1
0
Order By: Relevance
“…The horseshoe kidney is the most common type of renal fusion anomaly, and its prevalence has been reported as between 0.1% and 0.3% in the literature [17,18]. In our study, 10 patients in total presented with with horseshoe kidneys, and the prevalence was determined as 0.6%, which is close to the rate stated in the literature.…”
Section: Discussionsupporting
confidence: 85%
See 1 more Smart Citation
“…The horseshoe kidney is the most common type of renal fusion anomaly, and its prevalence has been reported as between 0.1% and 0.3% in the literature [17,18]. In our study, 10 patients in total presented with with horseshoe kidneys, and the prevalence was determined as 0.6%, which is close to the rate stated in the literature.…”
Section: Discussionsupporting
confidence: 85%
“…Ichikawa et al [20] revealed in an another study that the total venous anomaly rate was 28.6% in patients with horseshoe kidneys and evaluated it as higher than the normal population. Leblebisatan et al [18] reported that the variation rate was 5.18 times higher in patients with horseshoe kidneys of RLRV than those without. In our study, a total of four patients had IVC variation, but these patients did not have a horseshoe kidney.…”
Section: Discussionmentioning
confidence: 96%